Macroeconomic Patterns and Monetary Policy in the Run-up to Asset Price Busts - Scott, Alasdair (IMF Working Papers; Working Paper ;, 2009)
We find that inflation, output and the stance of monetary policy do not typically display unusual behavior ahead of asset price busts. By contrast, credit, shares of investment in GDP, current account deficits, and asset prices typically rise, providing useful, if not perfect, leading indicators of asset price busts. These patterns could also be observed in the build-up to the current crisis. Monetary policy was not the main, systematic cause of the current crisis. But, with inflation typically under control, central banks effectively accommodated these growing imbalances, raising the risk of damaging busts.